En face swept-source optical coherence tomography (SS-OCT) and SS-OCT angiography findings of retinal astrocytic hamartomas in patients with tuberous sclerosis complex - Zhang, Chen-Xi; Xu, Kai-Feng; Long, Qin; Zhang, Xiao; Yang, Zhi-Kun; Dai, Rong-Ping; Zhang, Zhi-Qiao (Frontiers in Medicine, 2025)
IntroductionTuberous sclerosis complex (TSC) is an autosomal dominant disorder characterized by multisystem hamartomas, including retinal astrocytic hamartomas (RAHs), which are a key diagnostic criterion. This study evaluates the en face swept-source optical coherence tomography (SS-OCT) and SS-OCT angiography (SS-OCTA) features of TSC-associated RAHs.MethodsA retrospective analysis of 10 patients with TSC-associated RAHs was conducted using en face SS-OCT, SS-OCTA, and fundus photography. Structural and vascular features of the lesions were assessed based on these imaging modalities.ResultsOf the 10 TSC patients, 21 RAH lesions (18 type 1, 1 type 2, 2 type 3) were completely scanned. En face SS-OCT revealed vitreous changes in 17 of the 21 RAH lesions, with clear visualization of vitreoretinal traction in 6 lesions. Type 1 RAHs appeared as isoreflective or mildly hyporeflective masses with disarrangement of retinal nerve fibers. Calcified components in type 2 or type 3 RAHs appeared differently on the en face choroid slab, with type 2 RAHs featuring closely arranged isoreflective vesicles, while type 3 RAHs appeared as sharply defined dark areas. On SS-OCTA, a dense vascular network with disorganization of the radial papillary capillaries was observed in almost all of the type 1 RAHs, with half of them exhibiting congestive intrinsic microvasculature. Feeder vessels were identified in only two type 1 lesions. Non-flow, moth-eaten cavities were characteristic of the calcified components of type 2 or type 3 RAHs. The tumor vascular density was positively correlated with tumor maximal thickness in type 1 RAHs (p = 0.037).ConclusionEn face SS-OCT provided a good display of RAH-related vitreoretinal traction and tumor calcification, while SS-OCTA, by clearly visualizing intratumoral vascularity, may assist in detecting signs of progressive tumor growth in TSC-associated RAHs.